Analisis Faktor-faktor Yang Mempengaruhi Keinginan Konsumen Untuk Melakukan Pembelian Online Di Kota Batam - Wisnu Yuwono; Junen Wiwi (Universitas Internasional Batam, 2021)
The main objective of this study was to determine the trust towards attitude towards online purchasing, and the effect of perceived quality, perceived price, attitude towards online purchasing on consumers' desire to make online purchases in Batam city. Respondents in the study were 259 samples using the purposive sampling method and the data were processed using the Partial Least Square (PLS) program. The results showed that trust had a positive significant effect on attitude towards online purchasing, then perceived quality, perceived price and attitude towards online purchasing had a significant positive effect on purchase intention. The conclusion of this study shows that purchase intention is influenced by several variables, either directly or through mediating variables. This conclusion provides recommendations for company management to always consider the above variables in increasing consumer interest in making online purchases.